This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Math 5125 Monday, December 5 Solutions to Sample Final Problems 1. (a) Define a ring homomorphism : F [ x ] F by ( f ) = f for f F and ( x ) = 1. Then is onto and ker = { p F [ x ]  p ( 1 ) = } . Clearly x 1 ker , and by the factor theorem, ker ( x 1 ) . Therefore ker = ( x 1 ) and we can now apply the fundamental homomorphism theorem to deduce that F [ x ] / ( x 1 ) = F as rings. Similarly F [ x ] / ( x + 1 ) = F . We conclude that F [ x ] / ( x 1 ) = F [ x ] / ( x + 1 ) as rings. (b) Suppose : F [ x ] / ( x 1 ) F [ x ] / ( x + 1 ) is an Rmodule isomorphism. Write I = ( x 1 ) . Then 0 6 = x + 1 + I F [ x ] / I (this is where we use that the characteristic of F is not 2), yet ( x + 1 + I ) = ( x + 1 ) ( 1 + I ) = 0 and we have a contradiction. (c) Set J = ( x 1 ) (an ideal of F [ x ] ) and define an F [ x 2 ]map : F [ x 2 ] F [ x ] / J by ( p ) = p + J for p F [ x 2 ] . Clearly is onto and ( x 2 1 ) ker , because x 2 1 J . Also p ( x 2 ) ker implies p ( x 2 ) J , hence if we set x = 1 we obtain p ( 1 ) = 0. By the factor theorem, we deduce that p ( x 2 1 ) and hence ker = ( x 2 1 ) . The fundamental homomorphism theorem now tells us that F [ x 2 ] / ( x 2 1 ) = F [ x ] / ( x 1 ) as F [ x 2 ]modules. Similarly F [ x 2 ] / ( x 2 1 ) = F [ x ] / ( x + 1 ) and we conclude that F [ x ] / ( x 1 ) = F [ x ] / ( x + 1 ) as F [ x 2 ]modules, so the answer is yes. 2. Note that J ( M / IM ) = ( IM + JM ) / IM . Thus N / JN = M / IM J ( M / IM ) = M / IM ( JM + IM ) / IM , hence by third isomorphism theorem, N / JN = M / ( JM + IM ) (cancel the IM s). Also JN = ( JM + IM ) / IM = JM / ( IM JM ) ....
View
Full
Document
This note was uploaded on 01/02/2012 for the course MATH 5125 taught by Professor Palinnell during the Fall '07 term at Virginia Tech.
 Fall '07
 PALinnell
 Algebra, Factor Theorem

Click to edit the document details